Production and spatial structure of Mediterranean pastures in different stages of ecological succession (Plant Ecology, 1986)
The aim of this paper is to describe the changes of Mediterranean pasture phytomass and their dependence on succession, slope geomorphology and herbivore consumption. Four neighbouring slopes of similar aspect and steepness, located in a pasture area of Central Spain, were chosen for sampling. The slopes had not been cultivated for 1, 3, 8 and 40 years respectively. On each slope both the upper, erosion zone and the lower, accumulation zone were sampled during the months of plant growth (April to July), phytomass being record- ed in plots where herbivore consumption was avoided with protection cages and in unprotected plots. Results from the protected plots show that the upper and lower parts of slopes undergo a different develop- ment during succession. The highest values of phytomass reached, tended to decrease during succession in the upper zones, the same being true for production. However in the lower zones both parameters tended to increase in time. The ratio P/B, widely known in ecology to decrease with time, did not seem to behave as a usual index of succession in the studied ecosystem. In the upper zone this ratio tended to decrease but in the lower zone it increased with succession after the first years. Phytomass consumption by herbivores was progressively concentrated during succession in the slope sec- tors of greater production, mainly in the lower zone, which increased its productivity as the slope-talweg sys- tem became functional. The evolution of the ecological structure of a slope should be interpreted not only as a result of the tolerance of species to phsysico-chemical factors. It may also reveal the existence of an im- portant interaction between the pasture and the grazing behaviour of exploiting animals. Multivariate analy- sis of phytomass records revealed a trend of temporal variation which should be identified with the progress